Analisis Logam Berat Pada Lahan Bekas Tailing Emas Berdasarkan Sifat Fisik Kimia Tanah - Syari Rahma Yanti; Rika Ampuh Hadiguna; Fitri Nauli; Arif Algifari; Tedy Agung Cahyadi; Rika Ernawati (Unversitas Muhammadiyah Mataram, 2024)
Abstract: Heavy metals are considered pollutants because its have a toxic effect on an organism if they exceed a certain concentration. The purpose of this study is to determine the characteristics of soil materials based on the physical and chemical properties of the soil. The method used to process the data is using the Soil Chemical Properties Assessment criteria while the texture class is determined based on the Texture Triangle. The result of the physical and chemical properties analysis of the soil is to determine the fertility level of the tailings soil. The analysis was carried out by assessing the physical properties of the soil, namely soil texture, while the assessment of soil chemical properties was soil pH, Cationic Exchange Capacity (CEC), Base Saturation (BS), C-Organic, and metal percentages of Potassium (K), Calcium (Ca), Magnesium (Mg), Sodium (Na). The results of the study showed that the tailings soil had a pH value of 8.89 including the lime category, this was in line with the CEC value and the alkaline saturation was classified as high and very high with values of 31.33% and 94.67 cmol/kg, as well as the values of Potassium (K), Calcium (Ca), Magnesium (Mg), Sodium (Na) which showed very high amounts in the results of the TSF 56 tailings soil testing laboratory. However, the value of C-Organic content is 0.16%, including a very low category. The permeability value of tailings soil is quite low, which is 0.21%, this is in line with the texture of tailings soil which is dominated by clay and dust so that the ability to drain water is very low.Abstrak: Logam berat dianggap sebagai pencemar karena memiliki efek racun pada suatu organisme apabila sudah melebihi konsentrasi tertentu. Tujuan dari penelitian ini adalah untuk mengetahui karakteristik material tanah berdasarkan sifat fisik dan kimia tanah. Metoda yang digunakan untuk mengolah data adalah menggunakan kriteria Penilaian Sifat Kimia Tanah sedangkan kelas tekstur ditentukan berdasarkan motoda Segitiga Tekstur. Hasil dari analisis sifat fisik dan kimia tanah adalah untuk mengetahui tingkat kesuburan tanah tailing. Analisis dilakukan dengan menilai sifat fisika tanah yaitu tekstur tanah, sedangkan penilaian sifat kimia tanah yaitu pH tanah, Kapasitas Tukar Kation (KTK), Kejenuhan Basa (KB), C-Organik, dan persentaase logam Kalium (K), Kalsium (Ca), Magnesium (Mg), Natrium (Na). Hasil penelitian menunjukkan tanah tailing memiliki nilai pH sebesar 8.89 termasuk kategori kalis, hal ini sejalan dengan nilai KTK dan kejenuhan basa tergolong tinggi dan sanggat tinggi dengan nilai 31,33 % dan 94,67 cmol/kg, begitupun dengan nilai Kalium (K), Kalsium (Ca), Magnesium (Mg), Natrium (Na) yang menunjukan jumlah yang sanggat tinggi pada hasil laboratorium pengujian tanah tailing TSF 56. Namun untuk nilai kandungan C-Organik adalah 0.16% termasuk katagori sangat rendah. Untuk nilai permeabilitas tanah tailing cukup rendah yaitu 0.21 %, ini sejalan dengan tesktur tanah tailing yang didominasi oleh liat dan debu sehingga kemampuan melolokan air sangat rendah.